Pengaruh Latihan Zig-Zag terhadap Kelincahan Menggiring Bola pada Permainan Sepak Bola Siswa Putra di SMA Negeri Suwawa - Ruslan Ruslan; Ella H. Tumaloto (Departement of Mathematics Education, 2023)
This study aims to determine whether there is an effect of zig-zag training on the agility of dribbling soccer in male students of SMA Negeri 1 Suwawa. The method used is an experimental technique with a One Group Pretest posttest design. The sample used was all male students with a total of 104 people. Data analysis used the normality test using the Lilefors test and hypothesis testing used the t-test. The result is that there is an effect of zig zag running training on dribbling agility in soccer at SMA Negeri 1 Suwawa with the result tcount = 14.56 > ttabel = 1.6597.